Peptidoglycan Recognition Peptide 2 Aggravates Weight Loss in a Murine Model of Chemotherapy-Induced Gastrointestinal Toxicity - Bech, Ann-Sophie; Nexoe, Anders Bathum; Dubik, Magdalena; Moeller, Jesper Bonnet; Soerensen, Grith Lykke; Holmskov, Uffe; Madsen, Gunvor Iben; Husby, Steffen; Rathe, Mathias (Frontiers in Oncology, 2021)
Introduction: Chemotherapy-induced gastrointestinal toxicity (CIGT) is a frequent, severe and dose-limiting side effect. Few treatments have proven effective for CIGT. CIGT is characterized by activation of the nuclear factor kappa B pathway which, leads to upregulation of proinflammatory cytokines. The innate immune protein peptidoglycan recognition peptide 2 (PGLYRP2) binds to and hydrolyzes microbial peptidoglycan. Expression of PGLYRP2 is upregulated in the intestine of chemotherapy-treated piglets. In this experimental study, we investigated the role of Pglyrp2 in the development and severity of murine CIGT. Methods:Pglyrp2 wildtype and Pglyrp2 knockout mice received intraperitoneal injections of chemotherapy (Doxorubicin 20 mg/kg) to induce CIGT. Weight was monitored daily, and animals were euthanized after 2 or 7 days. Expression of proinflammatory cytokines in the jejunum was measured by quantitative real-time polymerase-chain reaction and enzyme-linked immunosorbent assay. Villus height, crypt depth, and histologic inflammation were evaluated on haematoxylin and eosin stained tissue specimens. Results: Chemotherapeutic treatment induced weight loss (p < 0.05), shortening of the small intestine (p < 0.05), elongation of villus height (p < 0.05), increased crypt depth (p < 0.05), and led to elevated mRNA levels of II1β (p < 0.05), II6 (p < 0.05), and Tnf (p < 0.001) at day 2. Protein levels of IL1β, IL6, and TNFα did not change after exposure to chemotherapy. Doxorubicin treated wildtype mice had a more pronounced weight loss compared to knockout mice from day 3 to day 7 (D3-D6: p < 0.05 and D7: p < 0.01). No other phenotypic differences were detected. Conclusion:Pglyrp2 aggravates chemotherapy-induced weight loss but does not induce a specific pattern of inflammation and morphological changes in the small intestine.